Suppose EXP2 is an expression which happens to be a polynomial in one collection C of variables C_1,C_2,C_3,...C_n with coefficients depending on a collection D of variables D_1,D_2,...,D_m (EXP2=sum_{alpha in I}[A_alpha(D_1,D_2,...,D_m)*product_{k=1}^n[C_{alpha_k}^{alpha_k}]], where I is a finite index set in the set of n-tuples of integers and A_alpha is a coefficient). Suppose EXP1 is an expression which is equal to EXP2, but which is scrambled.
If I only have EXP1, how can I automatically rewrite it to be in the form of EXP2? Suppose, for example, that I have the code a=var('a') b=var('b') c=var('c') d=var('d') e=var('e') eqn=a==b*(d^2)+e*(c+d) + c*(2*b+e) How could I rearrage eqn automatically so that I am expressing a as a sum of b times a coefficent depending on c and d plus e times a coeffient depending on d and e, such that I get the equation a==b*(d^2+2*c)+e*(2*c+d)? -- You received this message because you are subscribed to the Google Groups "sage-support" group. To unsubscribe from this group and stop receiving emails from it, send an email to sage-support+unsubscr...@googlegroups.com. To post to this group, send email to sage-support@googlegroups.com. Visit this group at http://groups.google.com/group/sage-support. For more options, visit https://groups.google.com/d/optout.